Regulation of mycobacterial infection by macrophage Gch1 and tetrahydrobiopterin. Issue 1 (December 2018) - McNeill, Eileen; Stylianou, Elena; Crabtree, Mark; Harrington-Kandt, Rachel; Kolb, Anna-Lena; Diotallevi, Marina; Hale, Ashley; Bettencourt, Paulo; Tanner, Rachel; O'Shea, Matthew; Matsumiya, Magali; Lockstone, Helen; et al.
Abstract Inducible nitric oxide synthase (iNOS) plays a crucial role in controlling growth ofMycobacterium tuberculosis (M.tb ), presumably via nitric oxide (NO) mediated killing. Here we show that leukocyte-specific deficiency of NO production, through targeted loss of the iNOS cofactor tetrahydrobiopterin (BH4), results in enhanced control ofM.tb infection; by contrast, loss of iNOS renders mice susceptible toM.tb . By comparing two complementary NO-deficient models, Nos2 −/− mice and BH4 deficientGch1 fl/fl Tie2cre mice, we uncover NO-independent mechanisms of anti-mycobacterial immunity. In both murine and human leukocytes, decreasedGch1 expression correlates with enhanced cell-intrinsic control of mycobacterial infection in vitro. Gene expression analysis reveals thatGch1 deficient macrophages have altered inflammatory response, lysosomal function, cell survival and cellular metabolism, thereby enhancing the control of bacterial infection. Our data thus highlight the importance of the NO-independent functions ofNos2 andGch1 in mycobacterial control. Inducible nitric oxide (NO) synthase (iNOS) is essential in the response to mycobacterial infection, yet NOS signalling can occur through NO-dependent or NO-independent pathways. Here the authors show macrophage Gch1 and tetrahydrobiopterin mediate NO-independent control of Mycobacterial infection.